Evaluating the effectiveness of a health and environmental education training program for Syrian teachers in Northern Syria - Mervan Y. Huseyin; Abdulmuhaimen Dershewi; Debbi Marais; Marwan Albuhtori (International Journal of Educational Research Open)
In alignment with UNESCO's directives for ongoing teacher development in environmental awareness to achieve sustainable development goals, this study developed and evaluated a 14-week training curriculum aimed at enhancing Environmental and Health Education awareness among Syrian teachers. Fifty educators of both genders were selected to partake in a program tailored to their needs. The study employed a sequential explanatory mixed methods approach, which included pre- and post-testing; an online satisfaction survey as well as focus group discussions to explore the impact of the training. The findings revealed a statistically significant improvement in knowledge post-training, with average scores doubling from 31% to 65. The program received a high satisfaction rating of Very good-Excellent. Five themes emerged, namely acquired knowledge and skills, values instilled, personal and professional development and emerging topics. Participants overwhelmingly affirmed the training's value and impact, noting significant knowledge and value integration in Environmental and Health Education.